Business Process for debit card transactions using Electronic Data Capture (EDC) Case study: Bank CIMB Niaga Tbk - Samuel Andi Kristyan; Suhardi (Indonesia Journal on Computing (Indo-JC), 2024)
EDC (Electronic Data Capture) in banking is a means of expediting transactions at trade outlets. Sometimes not all buyers bring cash to buy the goods they want, usually the shop owner/keeper directs the buyer to withdraw money at an ATM or transfer using mobile banking or something similar. The problem that occurs is that sometimes there are queues at the ATM and not all buyers activate mobile banking. In fact, sometimes you don't end up buying an item that you have bargained for/liked, it's just a matter of a difficult transaction process. The presence of EDC banking machines can reduce the above problems. EDC is a transaction tool that is widely used today. Apart from ease of transactions, it also leaves several problems that need to be fixed. In this paper the author wants to analyze business processes and improvements so that they can minimize the risk of crime and lost property.